O rap na escola: contribuições para a leitura e a produção textual subsidiadas pela semiótica discursiva. - Aguiar, Mauro Sergio Gomes (Universidade Federal do Tocantins, 2022)
This paper discusses the possibility of using rap in Portuguese language classes at Basic Education, seeking to promote students' awareness of the situation of the discrimination that falls on social problems thematized in the lyrics of this genre musical. Rappers come from many populations living in suburban neighborhoods. of big cities, where certain minorities are confined by economic, social and and racial. In particular, we have in mind the proximity between this context thematized in the lyrics of rap and the reality of the peripheral neighborhoods of Araguaína. We live in a time of communication fast. Undoubtedly, verbal language, especially writing, occupies a prominent position in the world of communication, while there is a large number of young people without interest in reading, and consequently in school-related activities. There are many factors that explain this lack of interest, such as cell phone media and computers that point to more seductive universes than the one offered by the school in their more traditional practices of reading and writing. One proposal we support is the possibility of inserting music in the school scenario. Without wanting to interfere or belittle other genres, such as MPB, forró, samba, university sertanejo or axé, we indicate rap, or hip-hop, as it is a musical genre that encompasses an entire problematic of the social context of students participating in public schools in our State, seeking a form of involvement with reading and a more critical and meaningful. For the analysis of musical compositions, we mobilize semiotics discursive, a theory that focuses on understanding the processes of meaning, considering the articulations between an expression plane and a content plane. As if deals with a syncretic genre, we use productions from the semiotics of the song. Finally, we present some proposals for didactic guidance.